AKSI NYATA BERSIH-BERSIH SUNGAI DI DESA CANGKIR KECAMATAN DRIYOREJO KABUPATEN GRESIK - Samuji Samuji; Moch Fairuz Fahrezi A[-Haibah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
River Clean Action is a conservation effort focused on removing waste and other contaminants from rivers. This activity requires the involvement of different community groups, such as volunteers, NGOs, and local authorities. The primary objective of this initiative is to raise public awareness regarding the significance of maintaining rivers as a crucial natural resource. This initiative also aims to lessen harmful effects on aquatic ecosystems and enhance the quality of water available for local communities. Moreover, the River Clean Action serves as an educational tool for the community regarding responsible waste management methods and the significance of keeping the environment clean. By working together and engaging actively, this initiative aims to foster beneficial changes in community attitudes towards environmental conservation.